2016
DOI: 10.1021/acs.nanolett.6b02307
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation of Methylammonium Cations in Hybrid Organic–Inorganic Perovskite Solar Cells

Abstract: Organic-inorganic lead perovskites have shown great promise as photovoltaic materials, and within this class of materials (CH3NH3)PbI3-xClx is of particular interest. Herein we use soft X-ray spectroscopy and density functional theory calculations to demonstrate that the methylammonium cations in a typical photovoltaic layer may dissociate into a metastable arrangement of CH3I-Pb2 defects and trapped NH3. The possibility that other metastable configurations of the organic components in (CH3NH3)PbI3-xClx is rar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
53
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(56 citation statements)
references
References 42 publications
3
53
0
Order By: Relevance
“…These two C 1s peaks have been commonly observed in many perovskite thin films containing CH 3 NH 3 + cations . Our previous results using XPS and X‐ray absorption and emission spectroscopy have confirmed that peak A is from CH 3 NH 3 + , and peak B is assigned to a CH 3 + ‐type species . This is further supported by other related reports.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…These two C 1s peaks have been commonly observed in many perovskite thin films containing CH 3 NH 3 + cations . Our previous results using XPS and X‐ray absorption and emission spectroscopy have confirmed that peak A is from CH 3 NH 3 + , and peak B is assigned to a CH 3 + ‐type species . This is further supported by other related reports.…”
Section: Resultssupporting
confidence: 90%
“…This can be explained using our previously proposed dissociation model for CH 3 NH 3 PbI 3 : the CH 3 NH 3 + can dissociate into CH 3 + and NH 3 , and the latter escape from the surface. Our results demonstrate that although there are always competing reactions between CH 3 NH 3 + dissociation and the production of perovskite, the reaction rates differ significantly, leading to different film compositions. It is interesting that although Evap‐2 is intended to mimic the two‐step spin‐coating method (Spin‐2 film), it has the highest amount of CH 3 + concentration and the lowest N concentration.…”
Section: Resultsmentioning
confidence: 86%
“…Xu et al . reported the dissociation of MA into CH 3 I and NH 3 defects in a perovskite structure, as observed in the present work 25 . The comprehensive results obtained using a combination of in-situ GIWAXD, XPS, and NEXAFS spectroscopy measurements performed at high temperature showed that the orientation and decomposition of MA cations is strongly linked with the progress of thermal degradation in MAPbI 3 perovskite films.…”
Section: Resultssupporting
confidence: 84%
“…Xu et al . suggested that exposure to light (X-rays) creates dipole-aligned CH 3 -PbI 2 defects, which lead to strain in the lattice, eventually inducing collapse of the perovskite structure into PbI 2 and free CH 3 I and NH 3 25 . Aristidou et al .…”
Section: Introductionmentioning
confidence: 99%
“…The depth profile of NH − is exhibited to trace the existence of NH 3 . The intensity of NH − was rather low and barely changed after the thermal treatment, confirming the existence of the reported CH 3 I‐PbI 2 defects in the MAPbI 3 layer . But considering the massive CN − diffusion, we prefer to deduce that the main thermal decomposition products of the MAPbI 3 thin film in a whole PSC device are PbI 2 , MA + , and I − .…”
Section: Resultsmentioning
confidence: 99%